Study of pathological changes in placentas of gestational diabetes mellitus and its association with fetal outcome - Rani, A. Swarupa; Jacintha, B. Nissy; Khatoon, Khuteja; Harechandana, M.; Mamatha, Manchikanti (ScienceRise: Medical Science, 2022)
GDM is associated with an adverse fetal and neonatal outcome that often presents with macrosomia, birth trauma, neonatal hypoglycemia, and respiratory distress syndrome. The inclusion of GDM into ’the great obstetrical syndromes’ emphasizes the role of the placenta in interactions between the maternal and fetal unit. The aim: To study pathological changes in the placentas of gestational diabetes mellitus and its association with fetal outcome. Materials and methods: The Prospective study was conducted among pregnant women above the age of 18 years diagnosed with gestational diabetes attending the hospital. All patients are subjected to complete physical examination along with obstetric examination. All the routine investigations, including the complete blood counts, blood picture, RBS, RFT, LFT, OGTT, CUE and, ultrasonography with doppler, histopathological examination of the placenta after delivery. Results: The weight of the babies born to GDM mothers and normal mothers were compared, and the GDM mother’s baby weighed higher, meaning diabetes has an effect on the baby’s weight which was statistically significant. Comparison of the placenta was made for cases and controls; the result suggested all the morphological parameters placenta - weight (p<0.001), diameter (p<0.001), area (p<0.002) and thickness (p<0.001) were statistically significant. The complications reported were respiratory complications, hypoglycemia, hyperbilirubinemia, meconium staining, polycythemia, sepsis and hypocalcemia. Babies of gestational diabetic mothers have a higher risk of developing neonatal complications than non-diabetic mothers. Villous oedema, villous fibrosis, syncytial knots, and fibrinoid necrosis is seen on histopathological examination was <0.05, and hence there was a significant difference between these findings in both the groups. Conclusions: GDM is associated with the adverse fetal and neonatal outcome that often presents with respiratory complications, hypoglycemia, hyperbilirubinemia, meconium staining, polycythemia, sepsis and hypocalcemia. Including GDM into ’the great obstetrical syndromes’ emphasizes the role of the placenta in interactions between the maternal and fetal unit